Engineered Humicola insolens cutinase for efficient cellulose acetate deacetylation. Issue 8 (1st June 2017) - Shirke, Abhijit N.; Butterfoss, Glenn L.; Saikia, Rakhi; Basu, Aditya; de Maria, Leonardo; Svendsen, Allan; Gross, Richard A.
Abstract: Cutinases comprise a family of esterases with broad hydrolytic activity for chain and pendant ester groups. This work aimed to identify and improve an efficient cutinase for cellulose acetate (CA) deacetylation. The development of a mild method for CA fiber surface deacetylation will result in improved surface hydrophilicity and reactivity while, when combined with cellulases, a route to the full recycling of CA to acetate and glucose. In this study, the comparative CA deacetylation activity of four homologous wild‐type (wt) fungal cutinases from Aspergillus oryzae (AoC), Thiellavia terrestris (TtC), Fusarium solani (FsC), and Humicola insolens (HiC) was determined by analysis of CA deacetylation kinetics. wt‐HiC had the highest catalytic efficiency (≈32 [cm 2 L ‐1 ] ‐1 h ‐1 ). Comparison of wt‐cutinase catalytic constants revealed that differences in catalytic efficiency are primarily due to corresponding variations in corresponding substrate binding constants. Docking studies with model tetrameric substrates also revealed structural origins for differential substrate binding amongst these cutinases. Comparative docking studies of HiC point mutations led to the identification of two important rationales for engineering cutinases for CA deacetylation: (i) create a tight but not too closed binding groove, (ii) allow for hydrogen bonding in the extended region around the active site. Rationally designed HiC with amino acid substitutions I36S, predicted to hydrogen bond to CA, combined with F70A, predicted to remove steric constraints, showed a two‐fold improvement in catalytic efficiency. Continued cutinase optimization guided by a detailed understanding of structure‐activity relationships, as demonstrated here, will be an important tool to developing practical cutinases for commercial green chemistry technologies. Abstract : A comparative activity analysis of four wild type cutinases in conjunction with the substrate docking studies provided significant insights into structural features required for the cutinase catalyzed cellulose acetate deacetylation. A tight but not too closed binding groove in Humicola insolens Cutinase (HiC) contributes to its high binding constant making it the best performing cutinase. Further, Amino acid substitutions I36S, predicted to hydrogen bond to CA, combined with F70A, predicted to remove steric constraints, yielded a two‐fold improvement in catalytic efficiency of HiC.